Chrysin Attenuates High Glucose-Induced BMSC Dysfunction via the Activation of the PI3K/AKT/Nrf2 Signaling Pathway - Li Y; Wang X (Dove Medical Press, 2022)
Yu Li,1,2 Ximei Wang1 1Department of Plastic and Reconstructive Surgery, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People's Republic of China; 2Department of Hand, Plastic and Reconstructive Surgery, Burn Center-Hand and Plastic Surgery, University of Heidelberg, BG Trauma Center Ludwigshafen, Ludwigshafen, GermanyCorrespondence: Ximei WangDepartment of Plastic and Reconstructive Surgery, The First Affiliated Hospital of Zhengzhou University, No. 1 Longhu Middle Ring Road, Zhengzhou, 450018, People's Republic of ChinaTel +86 371-66278102Email tracywang@zzu.edu.cnPurpose: High glucose environment in diabetes mellitus induces the dysfunction of bone marrow-derived mesenchymal stromal cells (BMSCs) and impairs bone regeneration. Chrysin is a natural polyphenol with outstanding anti-inflammation and anti-oxidation ability. However, whether and how chrysin affects BMSCs in high glucose conditions remain poorly understood. The present study aimed to explore the effects and underlying mechanisms of chrysin on the BMSCs exposed to high glucose environment.Materials and Methods: Cell viability was detected by cell counting kit 8 assay and 5-ethynyl-2'-deoxyuridine staining, while cell apoptosis was determined through flow cytometry using Annexin V-FITC/PI kit. The oxidative stress in BMSCs was evaluated by detecting the reactive oxygen species production, malondialdehyde content, and superoxide dismutase activity. Alkaline phosphatase staining, Alizarin Red staining, and quantitative real-time PCR were performed to determine the osteogenic differentiation. Western blot was used to examine the expression of the PI3K/ATK/Nrf2 signaling pathway. Furthermore, chrysin was injected into calvarial defects of type 1 diabetic SD rats to assess its in vivo bone formation capability.Results: Chrysin reduced oxidative stress, increased cell viability, and promoted osteogenic differentiation in BMSCs exposed to high glucose. Blocking PI3K/ATK/Nrf2 signaling pathway weakened the beneficial effects of chrysin, indicating that chrysin at least partly worked through the PI3K/ATK/Nrf2 pathway.Conclusion: Chrysin can protect BMSCs from high glucose-induced oxidative stress via the activation of the PI3K/AKT/Nrf2 pathway, and promote bone regeneration in type 1 diabetic rats.Keywords: chrysin, type 1 diabetes mellitus, hyperglycemia, bone regeneration